Functional traits and comparative transcriptomic insight into Pleurotus mushroom for improved cultivation in Malaysia - Leong, Chia Choong (2024)
Edible mushrooms are recognised as a functional food due to their rich content of bioactive substances and low calories. Pleurotus, or oyster mushroom contributes to a quarter of global mushroom production while the most cultivated mushroom in Malaysia is Pleurotus pulmonarius. The mushroom industry is constantly facing challenges arising from mushroom spawn of low quality. To maximize production, it is therefore essential to use strains with excellent biological efficiency, measured by the fresh weight of mushroom per dry substrate used. However, the biological and biochemical process at the molecular level that underlies the biological efficiency of P. pulmonarius are not well-known. This research aims to identify and determine the differentially expressed genes and transcriptome profiles of selected Malaysian low- and high-yield Pleurotus pulmonarius strains. The association between antioxidant activities, nutritional profile, and biological efficiencies of Pleurotus strains were established. Mechanism underlying the biological efficiency and complete growth of selected P. pulmonarius samples was further investigated through transcriptomic profiling. By using three newly developed DNA barcodes, sixteen strains were identified as Pleurotus pulmonarius and eight as Pleurotus eryngii. Generally, P. pulmonarius showed antioxidant activities and phytochemical contents that were superior to P. eryngii. Biological efficiencies of ten identified P. pulmonarius strains were further established. Subsequently, comparative transcriptomic profiling was performed, with MP35 and MP42 classified as the high-yield type, whereas MP12 and MP28 designated as the low-yield type based on findings from the biological efficiency assessments. Differential expression analysis revealed 27449 unigenes exhibiting significant (P<0.05) dysregulation, where 13707 genes were upregulated and 13742 were downregulated in the high-yield group as compared to the low-yield group. Through KEGG enrichment analysis, four potential differential expressed gene were discovered. Aspartyl protease, CATALASE1, GTPase activating protein SEC23, palmitoyltransferase and copper amine oxidase from various significantly enriched pathways were verified using real time polymerase chain reaction (qPCR). Palmitoyltransferase, copper amine oxidase and CATALASE1 were downregulated while GTPase-activating protein and aspartyl protease were upregulated according to NGS results. The relative gene expression from qPCR results follows the same trend for each gene. The application of the identified five genes can be used as molecular biomarkers to differentiate high and low yield P. pulmonarius strain before large-scale commercial cultivation. These results provide valuable information on species identification, strain selection and cultivation strategies of P. pulmonarius for improving mushroom agriculture industry.